Effect of oilseed radish extract on the incidence of thrips, Thrips tabaci Lind., and onion yield in organic farm system (Revista de Ciências Agroveterinárias, 2007)
The objective of this research was to evaluate the effect of oilseed radish extract, Raphanus sativus L. var. oleiferus Metzg., on the incidence of thrips, Thrips tabaci Lind., and onion yield in organic farm system. Treatments were oilseed radish extract at 3, 5 and 10%, and untreated control plot. The incidence of thrips, the onion yield and bulb weight did not differ among treatments. The extract rates had a significant linear relation with onion bulb weight.
Keywords: insect; organic agriculture; agroecology; Allium cepa; Raphanus sativus L. var. oleiferus Metzg.